Current problems of arranging shelters in educational institutions in Ukraine - O. Kaidanovska; P. Dumnych (Architectural Studies, 2023)
This study covered the issue of creating safe conditions for all participants of the educational process in educational institutions in conditions of potential danger. The topic has become particularly relevant since 2022 as a result of the armed aggression of the Russian Federation against Ukraine. The arrangement of simple shelters (fortifications) in existing school buildings is decided by state authorities, legislative structures, regional institutions, and school administrations. The purpose of this study was to comprehensively examine the problem of creating a safe learning environment, identify indicative research areas, establish legislative guidelines, and preventively assess the real needs of protective structures to ensure the educational process at school. The study used the initial analysis of legal provisions, general scientific methods, systematisation and generalisation of special information, empirical methods, the method of expert assessments, factor analysis (for consideration of architectural solutions), and an interdisciplinary review of the provisions of the educational process security. The stages of solving the problem of designing and building shelters in educational institutions of Ukraine were outlined. The main factors in the formation of architectural solutions for shelters and the safety of the educational process were identified as follows: legislative; organisational; architectural and planning; engineering and technical; pedagogical; and daily. The scientific and pedagogical principles were addressed, the study highlighted the modern trends and innovative models of school education that influence the architectural organisation of school buildings. Planning solutions should provide for variant ergonomic organisation of the educational process, open educational, communication, and recreational spaces. It was emphasised that the educational environment of a school should consider security requirements. The study examined the case of a newly built school with a shelter for pupils and teachers that has adequate conditions for learning. The practical value of the study lies in the possibility of applying certain aspects and conclusions in the real design of educational institutions based on a comprehensive consideration of security requirements